Gambaran Status Mutu Tata Kelola Rantai Dingin Vaksin Covid-19 di Kabupaten Kotawaringin Timur - Hidayat, Muhammad Rizky; Saraswati, Lintang Dian; Kusariana, Nissa; Udijono, Ari (Jurnal Riset Kesehatan Masyarakat, 2022)
Abstrak: The Covid-19 vaccination is one of the efforts of the Indonesian government to reduce the cases of Covid-19 infection. The success of vaccination is supported by proper cold chain management. There has been no similar research conducted in East Kotawaringin Regency, Central Kalimantan. Research conducted in Yogyakarta and Sarolangun showed that not all cold chain officers had implemented the vaccination guidelines. This study aims to provide an overview of the quality of the Covid-19 vaccine cold chain management. Method: The design of this research is descriptive observational. The data collection technique was carried out by interview method using a questionnaire instrument and direct observation of 13 cold chain management officers in East Kotawaringin Regency. Result: From the results of the study, all respondents were not equipped with cold chain tools according to the provisions. Conclusion: It can be concluded that the officers who manage the cold chain have not yet fully implemented the technical instructions for implementing the Covid-19 vaccination. The officers are expected to be able to manage the cold chain in accordance with the instructions of the directorate general of disease control and prevention of the Indonesian Ministry of Health